Repeatability and reproducibility of relative cerebral blood volume measurement of recurrent glioma in a multicentre trial setting. (June 2019) - Smits, Marion; Bendszus, Martin; Collette, Sandra; Postma, Linda A.; Dhermain, Frederic; Hagenbeek, Rogier E.; Clement, Paul M.; Liu, Yan; Wick, Wolfgang; van den Bent, Martin J.; Heiland, Sabine
Abstract: Background: Measurement of relative cerebral blood volume (rCBV) with dynamic susceptibility contrast (DSC) magnetic resonance imaging (MRI) is used extensively for brain tumour diagnosis and follow-up. The aim of this pilot study was to assess the robustness of rCBV measurement in patients with enhancing recurrent glioma in a European multicentre trial setting. Methods: We included pre-treatment postcontrast T1 weighted (T1w) and DSC scans of 20 patients with recurrent glioma from 2 European Organisation for Research and Treatment of Cancer trials (26101 and 26091). Three reviewers independently placed a fixed circular region of interest of 70 mm 2 in the tumour area of highest rCBV (rCBVmax ). To calculate the normalised rCBVmax (nrCBVmax ), three ROIs were placed in the anterior, middle and posterior centrum semiovale normal-appearing white matter of the contralateral hemisphere. After several months, each observer repeated the assessments blinded for initial findings. Repeatability and reproducibility were estimated with a mixed model. Each measurement was also classified according to 4 clinically meaningful categories. Results: Three patients were post hoc excluded from analysis because of lack of enhancing tumour. The mean nrCBVmax repeatability was 49.5%, and reproducibility was 5.5%. In 14 of 17 patients, at least 2 reviewers classified the patient into the same category. Conclusions: Our results indicate that a well-established review process needs to be applied upfront to assess perfusion in a multicentre trial setting. While awaiting further validation, we propose as a strategy to measure rCBV in the context of recurrent glioma trials to use two central reviewers and an adjudicator in case of disagreement. Highlights: Glioma perfusion measurement is only modestly repeatable and reproducible. Most tumours were classified in the same perfusion category by 2 reviewers. Relative cerebral blood volume reference values should be used with great care. In clinical trials, categorisation should be performed by at least two readers.